A protocol for correlating penetration resistance of Swedish weight sounding test and relative density of Porac sand using testing chamber - Gargullo, John Michael B.
Swedish Weight Sounding Test (SWST) is one of the most common and oldest soil penetration testing technique. This test has been utilized as a part of the soil investigation program and tool for liquefaction and landslide assessment in Japan, Australia, and New Zealand, among other countries. This had also been used in Japan to estimate the shear strength parameters of the soils are recommended by the Japan Housing Quality Act of 2000. Despite the advantages of technology in terms of portability and cost, it has been rarely used in the Philippines. This study presents the development of correlation between penetration resistance of Swedish Weight Sounding Test and Porac Sand Parameters using a testing chamber. SWST was conducted on reconstituted Porac and samples. A large reconstituted sand sample was prepared using air pluviation and side tamping. The pluviation system utilized in the study is composed of a storage tank, with a perorated plate and 2 layers of diffuser sieves. Based on the results of air pluviation, reconstituted sample with relative density ranging from 23% to 50%, indicate of loose to medium dense relative condition. Moreover, soil sample reconstituted using side tamping has a relative density ranging from 45.8% to 61.2%, indicative of the medium dense relative condition. Based on the results of SWST on the reconstituted samples, the average number of half turns for loose to medium dense sand sample are 4.5 and 8.3, respectively. These are approximately equivalent to Nsw of 18 and 33. Furthermore, the average number of half turns and Nsw for medium dense sands is 19.3 and 77, respectively.